Validity and Reliability of Turkish version of Vaccination Confidence Scale for Parents - (:unkn) unknown (ISTANBUL UNIV-CERRAHPASA, 2020)
Aim: The aim of this study was to conduct a validity and reliability of the Vaccination Confidence Scale and to determine the knowledge, attitudes, and behavior of parents regarding childhood vaccinations. Method: This methodological study consisted of parents of 8th grade students in three districts of Istanbul from March 1 to May 1, 2017 (n=263). Data were collected using a questionnaire developed by the researcher and the Vaccination Confidence Scale. Results: The Vaccination Confidence Scale was found to be valid and reliable in this study. Seventy-six percent of the parents had had their children vaccinated with all the vaccines that the Ministry of Health recommended. There was no statistical difference between the overall score and the subscale scores of the parents on the Vaccination Confidence Scale (p>0.05). Conclusion: The Vaccination Confidence Scale may be used to assess the confidence parents have in vaccinations. Healthcare professionals should accurately inform families about vaccination calendars so that vaccinations can be carried out in time.
Keywords: Attitude; immunization; parents; Vaccination Confidence Scale; CITY